“Keep Holy Distance and Abstain till He Comes”: Interrogating a Pentecostal Church's Engagements with HIV/AIDS and the Youth in Kenya - Parsitau, Damaris Seleina (Africa Today, 2009)
The Deliverance Church in Kenya has attempted to provide moral solutions to the HIV/AIDS pandemic by promoting behavioral change among the youth: it teaches abstinence before marriage and fidelity within marriage and requires mandatory HIV testing for those intending to get married. Such teachings confine HIV/AIDS to issues of sex, obscure the complexity of sexuality, and ignore social, economic, and political situations that fuel the spread of the virus. In this response, the church has entered into a contested moral minefield, in which it is attempting socially and sexually to discipline its members, particularly its youthful constituency. These messages reach many young people, who form the bulk of the membership of this church. Many strive to follow the church's teachings, but do not accept them uncritically, and some refuse to be morally disciplined by them.
Free